Enaminone-Directed Rh(III)-Catalyzed Hydroarylation Reaction of Oxa/azabenzonorbornadienes through C–H Bond Functionalization - Ahire, Milind M.; Belani, Jitendra D. (Synlett, 2025)
We report an Rh(III)-catalyzed hydroarylation of oxa- and azabenzonorbornadienes directed by enaminones through C–H activation. The reaction proceeds under mild conditions with broad substrate scope and excellent regioselectivity. Diverse polycyclic products are obtained in high yields. A representative structure was confirmed by X-ray analysis.
Keywords: C–H activation; Rhodium catalysis; Enaminone; Hydroarylation; Oxa/azabenzonorbornadienes